Sodium-ion battery positive electrode additive, preparation method and material thereof, pole piece and battery
By introducing an oxygen-rich vacancies perovskite-type hypoxic oxide structure doped with lanthanum and fluorine into the positive electrode of the sodium ion battery, the problem of irreversible capacity loss in the electrochemical cycle of sodium ion battery is solved, and the circulation performance and energy density of the material are significantly improved.
Patent Information
- Application Number
- CN202411676381.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-11
AI Technical Summary
There is an irreversible capacity loss problem in the electrochemical cycle of sodium ion batteries, mainly due to the SEI film formed by the electrolyte decomposition, the capture of sodium ions by structural defects and side reactions of the electrolyte.
Using the preparation method of sodium ion battery positive electrode additive, an intermediate transition layer material with a perovskite-type hypoxic oxide structure rich in oxygen vacancies is prepared by grinding and mixing the sodium source, lanthanum source, chlorine source and fluorine source under an inert atmosphere, and calcining at high temperature.
By introducing high-valent lanthanum and halogen fluorine elements, the high voltage cycling and rate performance of the material is improved, the energy density and power density of the material are significantly improved, and irreversible structural changes and interface side reactions are suppressed.
Smart Images

Figure CN119591142A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy batteries, and in particular to a sodium ion battery positive electrode additive and a preparation method thereof, a sodium ion battery positive electrode material, a sodium ion battery positive electrode sheet and a sodium ion battery. Background Art
[0002] Sodium ion battery is also a kind of "rocking chair battery". The working principle of sodium ion battery is basically the same as that of lithium ion battery. It also uses the reversible directional migration process of alkali metal ions between positive and negative electrodes to realize the charging and discharging of the battery. + The electrons are released from the positive electrode material and are transported through the separator by the electrolyte and embedded in the negative electrode material. The discharge process is the opposite. During the charge and discharge process, the same number of electrons are transferred through the external circuit and are + Migrate together between the positive and negative electrode materials to maintain charge balance.
[0003] In the existing sodium-ion battery electrode material system, the positive electrode mainly includes layered oxides, polyanion compounds and Prussian blue materials, and the negative electrode materials mainly include non-metallic elements (such as carbon, phosphorus, etc.), alloy materials, oxygen compounds, organic materials, etc., among which inorganic carbonaceous materials (hard carbon and soft carbon) are the most widely used.
[0004] Similar to the working principle of lithium-ion batteries, the electrode materials of sodium-ion batteries also have the problem of active sodium loss during electrochemical cycles, which leads to rapid decay of battery cycle performance. The main reasons for irreversible capacity loss in sodium-ion batteries are as follows:
[0005] 1) The electrolyte decomposes to form a solid electrolyte interface film (SEI film). The electrolyte of sodium ion batteries is mainly composed of carbonate solvents and sodium salts. The electrolyte is prone to irreversible decomposition reactions at low potentials to form SEI films, which leads to a decrease in the initial coulombic efficiency. For alloy negative electrode materials, due to the dramatic volume changes during the sodium storage process, the SEI film is constantly split and reconstructed during the cycle, resulting in further increase in sodium ion consumption;
[0006] 2) Capture of sodium ions by structural defects. There are a large number of structural defects in materials such as hard carbon, some of which can irreversibly capture sodium ions, resulting in irreversible loss of initial capacity;
[0007] 3) Sodium consumption caused by side reactions. The coordinated water contained in the positive electrode material is prone to side reactions with the electrolyte at high potential and cause sodium consumption. The positive electrode material undergoes repeated electrochemical deintercalation and stress, causing particle rupture, and the internal metal dissolves and reacts with the electrolyte to consume active sodium ions.
[0008] Based on the above problems, researchers have conducted in-depth research on materials and electrolyte design to reduce the irreversible capacity loss in sodium-ion batteries, but sodium consumption is difficult to completely eliminate. Therefore, pre-sodiumization of sodium-ion battery electrode materials has become an important solution to the above problems.
[0009] Pre-sodiumization and pre-lithiation have similar principles, that is, adding additional sodium ions before the battery works to compensate for the loss of active sodium ions and improve the coulombic efficiency of sodium ion batteries. At present, the pre-sodiumization methods are mainly concentrated in the positive electrode sodium supplementation, negative electrode sodium supplementation and electrolyte additives. Among them, the positive electrode sodium supplementation technology has a short cycle, low cost and good effect, making it the best solution for industrialization. There are many types of sodium-rich sodium supplementation additives, mainly inorganic compounds, including Na2CO3, NaN3, Na3P, NaCrO2, Na2C4O4, etc., but these positive electrode sodium supplementation additives have some shortcomings. For example, the theoretical capacity of Na2CO3 can reach 505mAh / g, but the actual capacity is less than 100mAh / g. NaN3 and Na3P are extremely unstable in the air, and the residual P may react with the active material or electrolyte to reduce the battery energy density.
[0010] In addition, in the prior art, for example, the invention patent CN 109585844A provides a sodium supplement in which -H in the benzene ring is replaced by -F, -Cl, -COOH, -CN or -NO and -ONa groups. This chemical substance with an organic sodium phenol structure not only has a low sodium supplement efficiency, but also the remaining organic benzene ring that is not easy to undergo electrochemical reaction after sodium removal is partially dissolved in the electrolyte, which has an adverse effect on the energy density and cycle performance of the battery; the invention patent CN112952037 B obtains a sodium-rich or over-sodium-rich positive electrode by reacting the positive electrode of a sodium ion battery with an aromatic sodium reagent solution in an inert atmosphere, thereby achieving an improvement in the battery energy density and cycle life, but the process has strict environmental requirements, and the sodium-rich effect depends on the weak controllability of the preparation process of the positive electrode sheet; the invention patent CN 115188967A mixes sodium salt, conductive agent and solvent, and sprays and granulates them to obtain composite sodium supplement material, which achieves the synergistic effect of sodium supplement and conductivity. However, since its sodium source is one or a combination of sodium carbonate and sodium bicarbonate, the high pH value is not conducive to homogenization and sheeting, and there is a safety hazard in the gas production after sodium removal inside the battery. Invention patent CN 115395116B provides a sodium ion battery composite electrode with sodium supplement function, which achieves the double-layer effect of conductivity and sodium supplement by mixing an inorganic sodium supplement composite agent with a second active material layer and uniformly coating it on the surface of the first active material layer. However, the sodium supplement composite agent in this process is a mixture of an inorganic sodium supplement agent and aluminum nitride, which is cumbersome and costly for the overall manufacturing of battery materials. Summary of the invention
[0011] The main purpose of the present invention is to provide a sodium ion battery positive electrode additive and a preparation method thereof, a sodium ion battery positive electrode material, a sodium ion battery positive electrode sheet and a sodium ion battery positive electrode, so as to solve the above technical problems.
[0012] To achieve the above object, the present invention provides a method for preparing a positive electrode additive for a sodium ion battery, comprising the steps of:
[0013] S1, according to the stoichiometric ratio Na 3-x A x O 1-δ Cl 1-y F y , grinding and mixing a sodium source, a lanthanum source, a chlorine source, and a fluorine source under an inert atmosphere; wherein a is a lanthanide rare earth element, 0<x≤0.1, 0<y≤0.2, and δ represents an imbalance of oxygen elements caused by changes in the surface structure during the annealing process;
[0014] S2, calcining the powder obtained in step S1 at 250-450° C. for 6-24 hours under sealed conditions, and crushing the powder after natural cooling to obtain a positive electrode additive for a sodium ion battery.
[0015] Furthermore, in step S1, according to the stoichiometric ratio of Na 3-x A x O 1-δ Cl 1-y F y After grinding the sodium source, lanthanum source, chlorine source and fluorine source under an inert atmosphere, the mixed powder is transferred to a ball mill lined with zirconia and ball milled at a speed of 300 to 1200 rpm for 3 to 10 hours.
[0016] Furthermore, the step S2 specifically includes: heating the powder obtained in step S1 to 250-450° C. at a rate of 3-20° C. / min under sealed conditions, calcining for 6-24 hours, and crushing after natural cooling to obtain the sodium ion battery positive electrode additive.
[0017] Further, the sodium source is at least one selected from sodium oxide, sodium hydroxide, sodium chloride, sodium fluoride, sodium acetate, sodium oxalate, sodium carbonate, sodium nitrate, sodium sulfate, sodium phosphate and sodium citrate; the lanthanum source is one or more selected from lanthanum hydroxide, lanthanum acetate, lanthanum nitrate hexahydrate, lanthanum carbonate, lanthanum acetylacetonate and lanthanum sulfate; the chlorine source is at least one selected from sodium chloride, ammonium chloride, lanthanum chloride, sodium hypochlorite, cyanuric chloride and other chlorine-containing organic substances; the fluorine source is at least one selected from sodium fluoride, sodium hydrogen fluoride, ammonium fluoride, polytetrafluoroethylene or polyvinylidene fluoride and other fluorine-containing organic substances; the inert atmosphere is one or more selected from nitrogen, argon or helium.
[0018] Furthermore, A is a lanthanum element; the sodium source is one or more selected from sodium oxide, sodium hydroxide, sodium chloride and sodium fluoride; the lanthanum source is one or more selected from lanthanum hydroxide, lanthanum carbonate and lanthanum fluoride; the chlorine source is one or more selected from sodium chloride, ammonium chloride, lanthanum chloride and sodium hypochlorite; the fluorine source is one or more selected from sodium fluoride, sodium bifluoride and ammonium fluoride.
[0019] The present invention also provides a sodium ion battery positive electrode additive, which is prepared by the preparation method of the sodium ion battery positive electrode additive described in any one of the above items.
[0020] The present invention also provides a sodium ion battery positive electrode material, which is used for an intermediate transition layer of a sodium ion battery composite positive electrode with a sandwich structure, wherein the intermediate transition layer material comprises the sodium ion battery positive electrode additive as described above.
[0021] The present invention also provides a sodium ion battery positive electrode plate, comprising a first active material layer, an intermediate transition layer and a second active material layer; the first active material layer and the second active material layer are both selected from at least one of transition metal oxides, Prussian blue and polyanionic compounds; the intermediate transition layer comprises the sodium ion battery positive electrode additive as described above; wherein the mass ratio of the first active material layer, the intermediate transition layer and the second active material layer is 45-90:9-45:1-10.
[0022] Furthermore, the first active material layer includes a metal layered oxide, and the second active material layer includes a polyanionic compound.
[0023] The present invention also provides a sodium ion battery, comprising the sodium ion battery positive electrode sheet as described in any one of the above items.
[0024] The present invention has at least the following beneficial effects:
[0025] 1) After the intermediate transition layer material is doped with high-valent lanthanide elements and annealed, an ion exchange reaction occurs at the interface, resulting in structural reconstruction to form a strong MO, and an oxygen-deficient oxide structure rich in oxygen vacancies perovskite is obtained. Under high voltage, the oxygen diffused from the bulk to the surface after the oxidation of the lattice oxygen of the positive electrode material can be filled, thereby inhibiting the irreversible structural changes and interface side reactions of the positive electrode material under high voltage, greatly improving the high voltage cycle performance and rate performance of the positive electrode material, and significantly improving the energy density and power density of the material;
[0026] 2) The doping of halogen F elements causes the sodium oxygen octahedron inside the crystal to be distorted, and the change in the Na-O bond length is conducive to the migration of sodium ions. At the same time, the fluorine-containing material has significant hydrophobicity and can effectively inhibit the charge recombination in surface defects;
[0027] 3) The sodium-rich anti-perovskite intermediate transition layer can prevent the first active material from producing gas to destroy the integrity of the pole piece structure, and can provide good buffering and stability for the pole piece externally, thereby achieving the effect of increasing and compensating the sodium ion migration rate, balancing the polarization uniformity of the two active layers, and improving the cycle performance and safety performance of the battery;
[0028] 4) A sodium-rich antiperovskite material with high ion conductivity was prepared by the solid-phase melting method. By introducing high-valent lanthanum and halogen fluorine doping, an oxygen vacancy-rich structure was obtained through interfacial ion exchange reaction after annealing heat treatment, which caused the sodium-oxygen octahedron inside the crystal to be distorted, effectively improving the stability of the material and the ion migration rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings are part of the present invention and are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention, but do not constitute an improper limitation of the present invention. Obviously, the drawings described below are only some embodiments. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the accompanying drawings:
[0030] Figure 1 It is a schematic flow chart of the preparation method of the positive electrode additive for sodium ion batteries in the present invention.
[0031] Figure 2 This is the XRD diagram of the sodium ion battery positive electrode additive in Example 1 of the present invention.
[0032] Figure 3 The diagram is a schematic diagram of the structure and process of the positive electrode sheet of the sodium ion battery of the present invention.
[0033] Figure 4 This is a comparison chart of the room temperature charge and discharge capacity retention rates of the full battery of the positive electrode sheet using the positive electrode additive of the sodium ion battery in Examples 1-6 of the present invention as the intermediate transition layer.
[0034] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0035] The following is a clear and complete description of the technical problems solved by the embodiments of the present invention, the technical solutions adopted, and the technical effects achieved in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other equivalent or obviously modified embodiments obtained by ordinary technicians in this field without creative work fall within the scope of protection of the present invention. The embodiments of the present invention can be concretized in a variety of different ways as defined and covered in the claims.
[0036] It should be noted that in the following description, many specific details are given for ease of understanding, but it is obvious that the present invention can be implemented without these specific details.
[0037] It should be noted that, in the absence of clear limitation or conflict, the various embodiments of the present invention and the technical features therein can be combined with each other to form a technical solution.
[0038] The preparation experiment of the sodium ion battery positive electrode additive provided in the present application includes Examples 1-6 and Comparative Examples 1-4, and specific experiments are carried out. The specific process parameters are shown in Table 1, and the experimental method includes:
[0039] First, a sodium source, a lanthanum source, a chlorine source and a fluorine source are weighed respectively according to a stoichiometric ratio of 2.9-3:0-0.1:0.8-1:0-0.2, mixed and ground under an inert atmosphere of nitrogen, and then ball-milled at a speed of 300-1200 rpm for 3-10 hours, and then transferred to a high-temperature muffle furnace and heated to 250-450° C. at a rate of 3-20° C. / min for calcination for 6-24 hours, and then naturally cooled and crushed to obtain the target product, sodium-rich antiperovskite material;
[0040] Table 1 Process parameters of Examples 1-6 and Comparative Examples 1-4
[0041]
[0042] The specific electrical performance test is performed according to the following process steps:
[0043] The sodium ion battery positive electrode additives prepared in Examples 1-6 and Comparative Examples 1-4 were applied to the charging intermediate transition layer in the sodium ion battery, and a composite electrode with a sandwich structure was designed and assembled into a sodium ion button battery for electrochemical characterization:
[0044] The sodium-rich anti-perovskite material prepared as above is applied to the charging intermediate transition layer in the sodium ion battery, and a composite electrode with a sandwich structure is designed, wherein the first active material and the second active material are both selected from at least one of transition metal oxides, Prussian blue and polyanionic compounds, wherein the mass ratio of the first active material: the intermediate transition layer: the second active material is 45-90:9-45:1-10, the first active material is preferably a metal layered oxide, and the second active material is preferably a polyanionic compound. The first active material, the second active material and the sodium-rich anti-perovskite material of the positive electrode are mixed with the binder PVDF and the conductive agent SP in a mass ratio of 90.0:5.0:5.0, and after being fully mixed with NMP as a solvent, they are uniformly coated on a metal aluminum foil in the order of the first active material layer, the intermediate transition layer and the second active material layer from the inside to the outside to prepare a positive electrode plate; hard carbon is used as the negative electrode material, the viscosity enhancer CMC, the binder is SBR, the conductive agent is SP, the mass ratio is 95.8:1.2:1.2:2.0, and deionized water is used as a solvent to prepare a slurry, which is then uniformly coated on a metal aluminum foil to prepare a negative electrode plate, and assembled into a soft-pack full battery with a capacity of 2.0Ah and injected with 1M NaPF6 organic solvent (EC:DEC:FEC=5:4:1) was used as the electrolyte, and the battery was charged and discharged at a constant current and constant voltage of 1C / 1C in the voltage range of 2.0 to 4.2V at room temperature (25℃±1) (charged at a constant current of 1C to 4.2V, and then charged at a low current of 0.05C at a voltage platform of 4.2V until charging was completed);
[0045] The resistivity of the sodium-rich antiperovskite material was tested by the four-probe method, and the sodium-supplemented material was pressed into a sheet at a pressure of 5 to 15 MPa to obtain a film-like material, which was connected to an electrochemical workstation at room temperature to test its ionic conductivity. The ionic conductivity can be calculated by the following formula:
[0046]
[0047] Among them, σ (S / cm) represents the ionic conductivity, S (cm2) represents the working electrode area of the battery (referring to the area of the positive electrode of the battery or the area of the negative electrode of the battery), l (cm) represents the thickness of the membrane material, and Rb is the resistance value of the material.
[0048] The electrical performance test results are shown in Table 2.
[0049] Table 2 Comparison of test data of Examples 1-6 and Comparative Examples 1-4
[0050]
[0051] Figure 2The XRD refinement diagram shows that the positions and intensities of the diffraction peaks of the sodium ion battery positive electrode additive prepared by the present invention are consistent with those of the standard card, the material has high crystallinity, small grain size, and no other impurities are generated, which is more conducive to the capture of diffuse oxygen and the breaking of Na-O bonds; Figure 4 From the comparison diagram of the room temperature charge and discharge capacity retention rate of the full battery of the positive electrode sheet with the sodium ion battery positive electrode additive as the intermediate transition layer in Examples 1-6 and Table 2, it can be seen that with the increase of the halogen fluorine content (Example 2 = Example 3 < Example 4 = Example 5), the ionic resistivity of the material also increases, indicating that the doping of halogen fluorine elements causes the sodium oxygen octahedron inside the crystal to be distorted, and the change in the Na-O bond length is conducive to the migration of sodium ions, thereby improving the ionic conductivity of the material; the increase in lanthanum content effectively suppresses the gas production after the battery cycle (Example 2 = Example 4 < Example 3 = Example 5), indicating that the oxygen-deficient oxide structure of the oxygen-free perovskite type rich in oxygen vacancies caused by lanthanum doping can fill the diffused oxygen from the bulk phase to the surface after the lattice oxygen of the positive electrode material is oxidized, thereby suppressing the irreversible structural changes and interface side reactions of the positive electrode material under high voltage, and greatly improving the high voltage cycle performance of the positive electrode material.
[0052] The embodiments described above are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included in the protection scope of the present invention.
Claims
1. A method for preparing a positive electrode additive for a sodium ion battery, characterized in that: Includes steps: S1, according to the stoichiometric ratio Na 3-x A x O 1-δ Cl 1-y F y , grinding and mixing a sodium source, a lanthanum source, a chlorine source, and a fluorine source under an inert atmosphere; wherein a is a lanthanide rare earth element, 0<x≤0.1, 0<y≤0.2, and δ represents an imbalance of oxygen elements caused by changes in the surface structure during the annealing process; S2, calcining the powder obtained in step S1 at 250-450° C. for 6-24 hours under sealed conditions, and crushing the powder after natural cooling to obtain a positive electrode additive for a sodium ion battery.
2. The method for preparing a positive electrode additive for a sodium ion battery according to claim 1, characterized in that: In step S1, according to the stoichiometric ratio of Na 3-x A x O 1-δ Cl 1-y F y After grinding the sodium source, lanthanum source, chlorine source and fluorine source under an inert atmosphere, the mixed powder is transferred to a ball mill lined with zirconia and ball milled at a speed of 300 to 1200 rpm for 3 to 10 hours.
3. The method for preparing a positive electrode additive for a sodium ion battery according to claim 1, characterized in that: The step S2 specifically includes: heating the powder obtained in step S1 to 250-450° C. at a rate of 3-20° C. / min under sealed conditions, calcining for 6-24 hours, and naturally cooling and then crushing to obtain the positive electrode additive for sodium ion batteries.
4. The method for preparing a positive electrode additive for a sodium ion battery according to claim 1, characterized in that: The sodium source is at least one selected from sodium oxide, sodium hydroxide, sodium chloride, sodium fluoride, sodium acetate, sodium oxalate, sodium carbonate, sodium nitrate, sodium sulfate, sodium phosphate and sodium citrate; the lanthanum source is one or more selected from lanthanum hydroxide, lanthanum acetate, lanthanum nitrate hexahydrate, lanthanum carbonate, lanthanum acetylacetonate and lanthanum sulfate; the chlorine source is at least one selected from sodium chloride, ammonium chloride, lanthanum chloride, sodium hypochlorite, cyanuric chloride and other chlorine-containing organic substances; the fluorine source is at least one selected from sodium fluoride, sodium hydrogen fluoride, ammonium fluoride, polytetrafluoroethylene or polyvinylidene fluoride and other fluorine-containing organic substances; the inert atmosphere is one or more selected from nitrogen, argon or helium.
5. The method for preparing a positive electrode additive for a sodium ion battery according to claim 1, characterized in that: The A is a lanthanum element; the sodium source is one or more selected from sodium oxide, sodium hydroxide, sodium chloride and sodium fluoride; the lanthanum source is one or more selected from lanthanum hydroxide, lanthanum carbonate and lanthanum fluoride; the chlorine source is one or more selected from sodium chloride, ammonium chloride, lanthanum chloride and sodium hypochlorite; the fluorine source is one or more selected from sodium fluoride, sodium hydrogen fluoride and ammonium fluoride.
6. A sodium ion battery positive electrode additive, characterized in that: The sodium ion battery positive electrode additive is prepared by the preparation method of any one of claims 1 to 3.
7. A sodium ion battery positive electrode material, characterized in that: An intermediate transition layer for a sodium ion battery composite positive electrode having a sandwich structure, wherein the intermediate transition layer material comprises the sodium ion battery positive electrode additive as claimed in claim 6.
8. A positive electrode plate for a sodium ion battery, characterized in that: It comprises a first active material layer, an intermediate transition layer and a second active material layer; the first active material layer and the second active material layer are both selected from at least one of transition metal oxides, Prussian blue and polyanionic compounds; the intermediate transition layer comprises the sodium ion battery positive electrode additive as claimed in claim 6; wherein the mass ratio of the first active material layer, the intermediate transition layer and the second active material layer is 45-90:9-45:1-10.
9. The positive electrode plate of a sodium ion battery according to claim 8, characterized in that: The first active material layer includes a metal layered oxide, and the second active material layer includes a polyanionic compound.
10. A sodium ion battery, characterized in that: It comprises a positive electrode plate for a sodium ion battery as described in any one of claims 8 to 9.
Citation Information
Patent Citations
Sodium-supplemented positive electrode active material, positive electrode material, sodium ion battery and preparation and use thereof
CN109585844A
A pre-sodium-treated sodium-ion battery cathode, its pre-sodium treatment method, and its application.
CN112952037B
Preparation method of anode sodium supplementing agent
CN115188967A
A sodium-ion battery positive electrode sheet and its preparation method, sodium-ion battery
CN115395116B